ANALISA HUBUNGAN STRUKTUR MODAL DENGAN ECONOMIC VALUE ADDED ( EVA ) GUNA MENILAI KINERJA PERBANKAN ( Studi Kasus Saham Lima Bank Terbesar Berdasarkan Aset dan Modal di BEJ tahun 2003 - 2004 ) - Anshari, Baddarruzaman (2005)
Economic Value Added (EVA) is a new approach to asses the performance of relatively new companies by focusing objectively on the shareholder's expectation. The implementation of the EVA concept in companies would assist them in evaluating their performance of whether the capital obtained from payables or stocks has their added value or not. A return of new investment can be said good only if the gain is bigger than its capital. EVA has its superiority in appraising a firm performance in an added value by taking account of its capital. A study result shows that a change of loan proportion has nothing to do with a change of EVA appraisal and neither does a change of asset. It means that a loan proportion will not decrease the value of EVA bank's, because EVA bank's depends on a capital source, cost, income just before interest and taxes, as well as other factors. And also, there isn't any influence between a change of share proportion and a change of EVA value. It would be much better if a decision making consider EVA value while allocating an asset or capital. EVA explicitly takes account of capital cost over a share and admits that the risk of capital cost over a share is bigger than over a loan. Management must be careful to prevent a capital addition from decreasing EVA value. Management must take the structure of capital, working average cost of capital, and source of capital in appraising EVA value.